Inhibition of the Growth of Plasmodium falciparum in Culture by Stearylamine-Phosphatidylcholine Liposomes - Gulam Mustafa Hasan; Neha Garg; Enna Dogra; Ranu Surolia; Prahlad Chandra Ghosh (Journal of Parasitology Research)
We have examined the effect of stearylamine (SA) in liposomes on the viability of Plasmodium falciparum in culture by studying the inhibition of incorporation of [3H]-hypoxanthine in the nucleic acid of parasites. Stearylamine in liposomes significantly inhibits the growth of the parasites depending on the phospholipids composition. The maximum inhibition was observed when SA was delivered through Soya phosphatidylcholine (SPC) liposomes. The chain length of alkyl group and density of SA in liposomes play a significant role in inhibiting the growth of the parasites. Incorporation of either cholesterol or Distearylphosphatidylethanolamine−Methoxy-Polyethylene glycol-2000 (DSPE-mPEG-2000) in Soya phosphatidylcholine-stearylamine (SPC-SA) liposomes improves the efficacy. Intraerythrocytic entry of intact SPC-SA liposomes into infected erythrocytes was visualized using fluorescent microscopy. No hemolysis was observed in uninfected erythrocytes, and slight hemolysis was noted in infected erythrocytes at high concentrations of SPC-SA liposomes. Overall, our data suggested SA in SPC-liposomes might have potential application in malaria chemotherapy.